Impact of Lactobacillus reuteri Supplementation on Anti-Helicobacter pylori Levofloxacin-Based Second-Line Therapy. (29th May 2012) - Ojetti, Veronica; Bruno, Giovanni; Ainora, Maria Elena; Gigante, Giovanni; Rizzo, Gianluca; Roccarina, Davide; Gasbarrini, Antonio
Abstract : Introduction . Helicobacter pylori eradication therapy has the potential burden of antibiotic-associated gastrointestinal (GI) side effects. The occurrence of side effects is among the major drawbacks of such regimens. GI manifestations may be related to alterations in the intestinal microflora. Probiotics can prevent or reduce antibiotic-associated side effects and have an inhibitory effect on H. pylori . Methods . To define the efficacy of Lactobacillus reuteri supplementation in H. pylori eradication and in preventing GI-associated side effects during a second-line levofloxacin triple therapy. 90 H. pylori -positive patients receive for 7 days a second-line triple therapy with esomeprazole, levofloxacin, and amoxicillin with L. reuteri for 14 days (group 1) and without probiotic supplementation (group 2). Each subject received a validated questionnaire to record symptoms everyday for 4 weeks from the start of therapy. H. pylori status and side effects were assessed 6 weeks after treatment. Results . The eradication rate was significantly influenced by probiotic supplementation with L. reuteri (group 1: 36/45, 80%; group 2: 28/45 62%; P < 0.05 ). The incidence of nausea and diarrhoea in group 1 was significantly lower than that in group 2. Conclusion . In H. pylori -positive subjects L. reuteri supplementation increases the eradication rate while reducing the incidence of the most common side effects associated with antibiotic therapy in second-line treatment.